168k views
4 votes
Which of the following is the product of (a + b)(a – b)?

Which of the following is the product of (a + b)(a – b)?-example-1
User Dasean
by
5.8k points

2 Answers

5 votes

Answer:

The correct answer is option B. a² - b²

Explanation:

To find (a + b)(a – b)

(a + b)(a – b) can be written as,

(a + b)(a – b) = a(a -b) + b(a - b)

(a + b)(a – b) = a*a - a*b + b*a -b*b

(a + b)(a – b) = a² - ab + ba - b²

(a + b)(a – b) = a² - ab + ab - b²

(a + b)(a – b) = a² - b²

Therefore the correct answer is option B. a² - b²

User Nisd
by
6.1k points
1 vote

Answer:

(a + b)(a – b)= a^2 - b^2

Explanation:

(a + b)(a – b)

We use FOIL method to multiply it

a*a = a^2

a * -b = -ab

+b * a = ab

b * -b = -b^2

Now we combine all the terms


a^2 - ab + ab + b^2

Here +ab and -ab are like terms

ab-ab becomes 0

So we are left with a^2 - b^2


User Heslacher
by
5.7k points